Experimental Study on the Spanwise Correlation of Vortex-Induced Force Using Large-Scale Section Model - Chunguang Li; Yu Mao; Yan Han; Kai Li; C.S. Cai (Shock and Vibration)
To investigate the spanwise correlation of vortex-induced forces (VIF) of a typical section of a streamlined box girder, wind tunnel tests of simultaneous measurement of force and displacement responses of a sectional model were conducted in a smooth flow. The spanwise correlation of VIF and pressure coefficients on the measurement points of an oscillating main deck were analyzed in both the time domain and frequency domain, respectively. The research results indicated that the spanwise correlation of VIF and pressure coefficients on the measurement points were related to the amplitudes of vortex-induced vibration (VIV), both of them weakened with the increase of spanwise distance; the maximum value of spanwise correlation coefficient is situated at the ascending stage of the lock-in region, rather than at the extreme amplitude point. The amplitudes of VIV showed different impacts on the spanwise correlation of pressure coefficients on the measurement points of the upper and lower surfaces, for which the maximum value of the spanwise correlation coefficients is located at the extreme amplitude point and the ascending stage of the lock-in region, respectively. Furthermore, the spanwise correlation of the pressure coefficients decreases continually from the upstream to downstream of the main deck; large coherence of vortex-induced forces and pressure appears around the frequency of vortex shedding, and the coherence of VIF and pressure becomes smaller with the increase in the spanwise distance.